Sustainment stories: a qualitative analysis of barriers to sustainment of the National Rural Transitions of Care Nurse Program - Mary Ava Nunnery; Heather Gilmartin; Michaela McCarthy; Lexus Ujano-De Motta; Ashlea Wills; Lynette Kelley; Christine D. Jones; Chelsea Leonard (BMC, 2022)
Abstract Background Understanding how to successfully sustain evidence-based care coordination interventions across diverse settings is critical to ensure that patients continue to receive high quality care even after grant funding ends. The Transitions Nurse Program (TNP) is a national intervention in the Veterans Administration (VA) that coordinates care for high risk veterans transitioning from acute care VA medical centers (VAMCs) to home. As part of TNP, a VA facility receives funding for a full-time nurse to implement TNP, however, this funding ends after implementation. In this qualitative study we describe which elements of TNP sites planned to sustain as funding concluded, as well as perceived barriers to sustainment. Methods TNP was implemented between 2016 and 2020 at eleven VA medical centers. Three years of funding was provided to each site to support hiring of staff, implementation and evaluation of the program. At the conclusion of funding, each site determined if they would sustain components or the entirety of the program. Prior to the end of funding at each site, we conducted midline and exit interviews with Transitions nurses and site champions to assess plans for sustainment and perceived barriers to sustainment. Interviews were analyzed using iterative, team-based inductive deductive content analysis to identify themes related to planned sustainment and perceived barriers to sustainment. Results None of the 11 sites planned to sustain TNP in its original format, though many of the medical centers anticipated offering components of the program, such as follow up calls after discharge to rural areas, documented warm hand off to PACT team, and designating a team member as responsible for patient rural discharge follow up. We identified three themes related to perceived sustainability. These included: 1) Program outcomes that address leadership priorities are necessary for sustainment.; 2) Local perceptions of the need for TNP or redundancy of TNP impacted perceived sustainability; and 3) Lack of leadership buy-in, changing leadership priorities, and leadership turnover are perceived barriers to sustainment. Conclusions Understanding perceived sustainability is critical to continuing high quality care coordination interventions after funding ends. Our findings suggest that sustainment of care coordination interventions requires an in-depth understanding of the facility needs and local leadership priorities, and that building adaptable programs that continually engage key stakeholders is essential.